Relationships between sprint, jumping and strength abilities, and 800 m performance in male athletes of national and international levels - Bachero-Mena, B.; Pareja-Blanco, F.; Rodriguez-Rosell, D.; Yanez-Garcia, J. M.; Mora-Custodio, R.; Gonzalez-Badillo, J. J. (Journal of Human Kinetics, 2017)
This study analysed the relationships between sprinting, jumping and strength abilities, with regard to 800 m running performance. Fourteen athletes of national and international levels in 800 m (personal best: 1:43-1:58 min:ss) completed sprint tests (20 m and 200 m), a countermovement jump, jump squat and full squat test as well as an 800 m race. Significant relationships (p < 0.01) were observed between 800 m performance and sprint tests: 20 m (r = 0.72) and 200 m (r = 0.84). Analysing the 200 m run, the magnitude of the relationship between the first to the last 50 m interval times and the 800 m time tended to increase (1st 50 m: r = 0.71; 2nd 50 m: r = 0.72; 3rd 50 m: r = 0.81; 4th 50 m: r = 0.85). Performance in 800 m also correlated significantly (p < 0.01-0.05) with strength variables: the countermovement jump (r = -0.69), jump squat (r = -0.65), and full squat test (r = -0.58). Performance of 800 m in high-level athletes was related to sprint, strength and jumping abilities, with 200 m and the latest 50 m of the 200 m being the variables that most explained the variance of the 800 m performance.